Optical glass and optical element

By optimizing the oxide reference composition of optical glass and controlling the content and molar ratio of each component, the problem of high Gd2O3 and Ta2O5 content in high refractive index optical glass is solved, and optical glass with high refractive index and low cost is realized, suitable for optical components manufacturing.

CN119176670APending Publication Date: 2024-12-24HOYA OPTICAL TECH (WEIHAI) CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310747832.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The total content of Gd2O3 and Ta2O5 in existing high-refractive index optical glasses is high, resulting in high cost, and it is necessary to develop optical glasses with low total content of Gd2O3 and Ta2O5 and high refractive index.

Method used

By optimizing the glass composition of the oxide reference, the content and molar ratio of components such as SiO2, B2O3, La2O3, Y2O3, TiO2, ZrO2, Nb2O5 are controlled, so as to ensure that the total content of Gd2O3 and Ta2O5 is below 3.50%, and at the same time, the refractive index is increased to form a high Optical glass with refractive index.

Benefits of technology

Optical glass with a small total content of Gd2O3 and Ta2O5 and a high refractive index is realized, reducing material costs and maintaining optical properties, making it suitable for the manufacturing of optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004300494230000171
    Figure BDA0004300494230000171
  • Figure BDA0004300494230000181
    Figure BDA0004300494230000181
  • Figure BDA0004300494230000191
    Figure BDA0004300494230000191
Patent Text Reader

Abstract

The present invention relates to an optical glass and an optical element, in a glass composition represented by mol% on an oxide basis, the content of SiO2 is 1.00% or more and 30.00% or less, the content of B2O3 is 1.00% or more and 40.00% or less, the content of La2O3 is 5.00% or more and 40.00% or less, the content of Gd2O3 is 0.00% or more and 3.50% or less, the content of Y2O3 is 0.50% or more and 20.00% or less, the content of TiO2 is 5.00% or more and 30.00% or less, and the content of ZrO2 is 0.00% or more and 20.00% or less. The content of Nb2O5 is from 0.00% to 20.00% (inclusive), the total content of Gd2O3 and Ta2O5 (Gd2O3 + Ta2O5) is from 0.00% to 3.50% (inclusive), the total content of La2O3, Gd2O3 and Y2O3 (La2O3 + Gd2O3 + Y2O3) is 26.50% or more, the total content of TiO2, ZrO2 and Nb2O5 (TiO2 + ZrO2 + Nb2O5) is from 23.00% to 36.00% (inclusive), the total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO + R2O) is 3.50% or more, the molar ratio of the content of Gd2O3 to the content of SiO2 (Gd2O3 / SiO2) is from 0.00 to 0.23 (inclusive), and the molar ratio of the content of the molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is from 0.80 to 1.56 (inclusive), the molar ratio of the SiO2 content to the La2O3 content (SiO2 / La2O3) is 0.87 or less, the molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is from 0.15 to 0.34 (inclusive), and the molar ratio of the TiO2 content to the B2O3 content (TiO2 / B2O3) is from 0.70 to 1.10 (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to optical glass and optical elements. Background Art

[0002] In recent years, optical glass having a high refractive index has been proposed as a material for optical elements (see, for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: WO2013 / 146378 Summary of the invention

[0006] Problems to be solved by the invention

[0007] Patent Document 1 (WO2013 / 146378) discloses a glass composition having a high combined content of Gd2O3 and Ta2O5 as a glass composition for achieving a high refractive index (see Examples of WO2013 / 146378). However, since Gd2O3 and Ta2O5 are expensive components whose unit prices have increased in recent years, in order to reduce the cost of glass, a glass having a low combined content of Gd2O3 and Ta2O5 is preferred.

[0008] In view of the above, one object of the present invention is to provide an optical glass having a low total content of Gd2O3 and Ta2O5 and a high refractive index.

[0009] Technical solutions to solve problems

[0010] An aspect of the present invention is as follows.

[0011] [1] An optical glass, wherein, in a glass composition expressed in mol % on an oxide basis,

[0012] The SiO2 content is 1.00% or more and 30.00% or less,

[0013] The B2O3 content is 1.00% or more and 40.00% or less,

[0014] The La2O3 content is 5.00% or more and 40.00% or less,

[0015] The Gd2O3 content is 0.00% or more and 3.50% or less,

[0016] The Y2O3 content is 0.50% or more and 20.00% or less,

[0017] The TiO2 content is 5.00% or more and 30.00% or less,

[0018] The ZrO2 content is 0.00% or more and 20.00% or less,

[0019] The Nb2O5 content is 0.00% or more and 20.00% or less,

[0020] The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more and 3.50% or less,

[0021] The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is more than 26.50%,

[0022] The total content of TiO2, ZrO2 and Nb2O5 (TiO2+ZrO2+Nb2O5) is 23.00% or more and 36.00% or less,

[0023] The total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more,

[0024] The molar ratio of the Gd2O3 content to the SiO2 content (Gd2O3 / SiO2) is greater than or equal to 0.00 and less than or equal to 0.23,

[0025] The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 0.80 or more and 1.56 or less,

[0026] The molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is 0.87 or less,

[0027] The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.15 or more and 0.34 or less, and

[0028] The molar ratio of the TiO2 content to the B2O3 content (TiO2 / B2O3) is greater than or equal to 0.70 and less than or equal to 1.10.

[0029] [2] The optical glass according to [1], wherein the Al2O3 content is greater than or equal to 0.00% and less than or equal to 2.00%.

[0030] [3] The optical glass according to [1] or [2], wherein the Nb2O5 content is greater than or equal to 0.10% and less than or equal to 20.00%.

[0031] [4] The optical glass according to any one of [1] to [3], wherein the WO3 content is 0.00% to 0.40%.

[0032] [5] The optical glass as described in any one of [1] to [4], wherein the total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less.

[0033] [6] The optical glass according to any one of [1] to [5], wherein the total content of the alkaline earth metal oxide RO and the alkali metal oxide R2O (RO+R2O) is 3.50% or more and 10.50% or less.

[0034] [7] The optical glass according to any one of [1] to [6], wherein the molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is greater than or equal to 0.17 and less than or equal to 0.34.

[0035] [8] The optical glass as described in any one of [1] to [7], wherein the molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is greater than or equal to 1.20 and less than or equal to 1.56.

[0036] [9] The optical glass as described in any one of [1] to [8], wherein the molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is greater than or equal to 0.50 and less than or equal to 0.87.

[0037]

[10] The optical glass as described in any one of [1] to [9], wherein the total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is greater than 0.00% and less than 2.50%.

[0038]

[11] The optical glass according to any one of [1] to

[10] , wherein

[0039] The Al2O3 content is 0.00% or more and 2.00% or less,

[0040] The Nb2O5 content is 0.10% or more and 20.00% or less,

[0041] The WO3 content is 0.00% or more and 0.40% or less,

[0042] The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less,

[0043] The total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more and 10.50% or less,

[0044] The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.17 or more and 0.34 or less,

[0045] The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 1.20 or more and 1.56 or less,

[0046] The molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is 0.50 or more and 0.87 or less, and

[0047] The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is greater than or equal to 0.00% and less than or equal to 2.50%.

[0048]

[12] An optical element comprising the optical glass according to any one of [1] to

[11] .

[0049] Effects of the Invention

[0050] According to one aspect of the present invention, it is possible to provide an optical glass having a low total content of Gd2O3 and Ta2O5 and a high refractive index, and an optical element composed of the optical glass. DETAILED DESCRIPTION

[0051] [Optical glass]

[0052] In the present invention and this specification, the glass composition of the optical glass is expressed as a glass composition based on oxides expressed in mol%. Here, the so-called "glass composition based on oxides" refers to a glass composition obtained by completely decomposing glass raw materials during melting and converting them into glass compositions existing as oxides in the glass. In the glass composition expressed in mol%, the glass composition is expressed on a molar basis (mol%, molar ratio). Hereinafter, for the glass composition expressed in mol%, "mol%" is also abbreviated as "%".

[0053] In the present invention and this specification, the content of a constituent component of 0%, 0.0% or 0.00%, or not contained or not introduced, means that the constituent component is substantially not contained, and the content of the constituent component is below the impurity level. Below the impurity level means, for example, less than 0.01%. "0%" can mean, for example, "0.0%" or "0.00%". The content of a certain component of "more than 0%, "more than 0.0%" or "more than 0.00%" means that the component is an arbitrary component.

[0054] The glass composition in the present invention and this specification can be obtained by methods such as ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). For example, quantitative analysis is performed on each element using ICP-AES. Then, the analysis value is converted into oxide records. The analysis value based on ICP-AES, for example, contains a measurement error of about ±5% of the analysis value. Therefore, the value recorded in the oxide converted from the analysis value also contains an error of about ±5%.

[0055] In the present invention and this specification, the refractive index refers to the refractive index nd of the d-line (wavelength 587.56 nm) of helium.

[0056] In the present invention and this specification, the Abbe number νd is used as a value indicating a property related to dispersion and is represented by the following formula.

[0057] νd=(nd-1) / (nF-nC)

[0058] In the above formula, nF is the refractive index of the F line (wavelength 486.13 nm) of blue hydrogen, and nC is the refractive index of the C line (656.27 nm) of red hydrogen.

[0059] Hereinafter, the above optical glass (may be simply described as “glass”) will be described in more detail.

[0060] <Glass Composition>

[0061] SiO2 is a glass network component. When its content increases, the viscosity of the glass increases, but the solubility tends to decrease. From the above viewpoints, the SiO2 content is 1.00% or more and 30.00% or less.

[0062] The SiO2 content is preferably above 2.00%, and more preferably above 3.00%, above 4.00%, above 5.00%, above 6.00%, above 7.00%, above 8.00%, above 9.00%, above 10.00%, above 11.00%, above 12.00%, above 13.00%, above 13.50%, above 14.00%, and above 14.50%.

[0063] In addition, the SiO2 content is preferably less than 29.00%, and more preferably less than 28.00%, less than 27.00%, less than 26.00%, less than 25.00%, less than 24.00%, less than 23.00%, less than 22.00%, less than 21.00%, less than 20.00%, less than 19.00%, less than 18.00%, less than 17.50%, less than 17.00%, and less than 16.50%.

[0064] B2O3 is a glass network component and is a component that helps improve melting properties. From the above viewpoints, the B2O3 content is 1.00% or more, preferably 2.00% or more, and more preferably 3.00% or more, 4.00% or more, 5.00% or more, 6.00% or more, 7.00% or more, 8.00% or more, 9.00% or more, 10.00% or more, 11.00% or more, 12.00% or more, 13.00% or more, 14.00% or more, 15.00% or more, 16.00% or more, 17.00% or more, 17.50% or more, 18.00% or more, 18.50% or more, 19.00% or more, and 19.50% or more.

[0065] On the other hand, when the content of B2O3 increases, the influence of volatilization becomes greater. Therefore, from the viewpoint of the ease of controlling optical properties, the content of B2O3 is 40.00% or less, preferably 39.00% or less, and more preferably 38.00% or less, 37.00% or less, 36.00% or less, 35.00% or less, 34.00% or less, 33.00% or less, 32.00% or less, 31.00% or less, 30.00% or less, 29.00% or less, 28.00% or less, 27.00% or less, 26.00% or less, 25.00% or less, 24.00% or less, 23.50% or less, 23.00% or less, and 22.50% or less.

[0066] Regarding the molar ratio of B2O3 content to SiO2 content (B2O3 / SiO2), if the value of this molar ratio becomes smaller, the glass tends to be highly dispersed, and if the value of this molar ratio becomes larger, the refractive index of the glass tends to decrease. From the above viewpoints, the molar ratio (B2O3 / SiO2) is greater than 0.80 and less than 1.56.

[0067] The molar ratio (B2O3 / SiO2) is preferably above 0.85, and more preferably above 0.90, above 0.95, above 1.00, above 1.05, above 1.10, above 1.15, above 1.20, above 1.21, above 1.22, and above 1.23.

[0068] In addition, the molar ratio (B2O3 / SiO2) is preferably 1.55 or less, and more preferably 1.54 or less, 1.53 or less, 1.52 or less, 1.51 or less, 1.50 or less, 1.49 or less, and 1.48 or less.

[0069] The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. Gd2O3 and Ta2O5 are components that increase the refractive index of glass, but from the perspective of reducing the cost of glass, the less the total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5), the better. The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) in the above-mentioned glass is 3.50% or less, preferably 3.00% or less, and more preferably 2.50% or less, 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, and 0.00% is the best.

[0070] The contents of Gd2O3 and Ta2O5 will be described later.

[0071] La2O3 is a component that contributes to high refractive index and low dispersion of glass. When the La2O3 content decreases, the refractive index tends to decrease, and when the La2O3 content increases, the glass tends to be easily crystallized. From the above viewpoints, the La2O3 content is 5.00% or more and 40.00% or less.

[0072] The La2O3 content is preferably above 6.00%, and more preferably above 7.00%, above 8.00%, above 9.00%, above 10.00%, above 11.00%, above 12.00%, above 13.00%, above 14.00%, above 15.00%, above 16.00%, above 17.00%, above 18.00%, above 19.00%, above 20.00%, above 20.50%, above 21.00%, above 21.50%, above 22.00%, and above 22.50%.

[0073] In addition, the La2O3 content is preferably less than 39.00%, and more preferably less than 38.00%, less than 37.00%, less than 36.00%, less than 35.00%, less than 34.00%, less than 33.00%, less than 32.00%, less than 31.00%, less than 30.00%, less than 29.00%, less than 28.00%, less than 27.50%, less than 27.00%, less than 26.50%, less than 26.00%, less than 25.50%, less than 25.00%, less than 24.50%, less than 24.00%, and less than 23.50%.

[0074] The content of Gd2O3 is above 0.00%, and can be 0.00%, above 0.00% or greater than 0.00%. Gd2O3 is a component that contributes to the high refractive index and low dispersion of glass. However, Gd2O3 is a component with a high unit price, and is also a component that increases the specific gravity, easily crystallizes the glass, and reduces the solubility of the glass. Therefore, when Gd2O3 is contained in the glass, it is preferably contained in the smallest amount possible. From the above viewpoints, the content of Gd2O3 is below 3.50%, and more preferably below 3.00%, below 2.50%, below 2.00%, below 1.50%, below 1.00%, below 0.50%, and preferably 0.00%.

[0075] Y2O3 is a component that contributes to the high refractive index and low dispersion of glass. However, when the Y2O3 content increases, there is a tendency for the glass to be easily crystallized. From the above viewpoints, the Y2O3 content is 0.50% or more and 20.00% or less.

[0076] The Y2O3 content is preferably 1.00% or more, and more preferably 2.00% or more, 3.00% or more, 3.50% or more, 4.00% or more, 4.50% or more, and 5.00% or more, respectively.

[0077] In addition, the Y2O3 content is preferably less than 19.00%, and more preferably less than 18.00%, less than 17.00%, less than 16.00%, less than 15.00%, less than 14.00%, less than 13.00%, less than 12.00%, less than 11.00%, less than 10.00%, less than 9.00%, less than 8.50%, less than 8.00%, less than 7.50%, less than 7.00%, less than 6.50%, less than 6.00%, and less than 5.50%.

[0078] From the viewpoint of increasing the refractive index of glass, the total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is above 26.50%, preferably above 27.00%, and more preferably above 27.50%, above 27.60%, above 27.70%, above 27.80%, above 27.90%, and above 28.00%, respectively.

[0079] From the viewpoint of inhibiting glass crystallization, the total content (La2O3+Gd2O3+Y2O3) is preferably less than 40.00%, and more preferably less than 35.00%, less than 34.00%, less than 33.00%, less than 32.50%, less than 32.00%, less than 31.50%, less than 31.00%, less than 30.50%, less than 30.00%, less than 29.50%, and less than 29.00%, respectively.

[0080] The molar ratio of the Gd2O3 content to the SiO2 content (Gd2O3 / SiO2) is 0.00 or more, and can be 0.00, 0.00 or more, or greater than 0.00. From the viewpoint of reducing the specific gravity of the glass, the molar ratio (Gd2O3 / SiO2) is 0.23 or less, preferably 0.22 or less, and more preferably 0.21 or less, 0.20 or less, 0.19 or less, 0.18 or less, 0.17 or less, 0.16 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, 0.11 or less, 0.10 or less, 0.09 or less, 0.08 or less, 0.07 or less, 0.06 or less, 0.05 or less, 0.04 or less, 0.03 or less, 0.02 or less, 0.01 or less, and preferably 0.00.

[0081] From the viewpoint of increasing the refractive index of glass, the molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is less than 0.87, preferably less than 0.85, and more preferably less than 0.80, less than 0.79, less than 0.78, less than 0.76, less than 0.75, less than 0.74, less than 0.73, less than 0.72, and less than 0.71, respectively.

[0082] The molar ratio (SiO2 / La2O3) can be greater than 0.00. From the viewpoint of maintaining the stability of the glass, it is preferably above 0.05, and more preferably above 0.10, above 0.15, above 0.20, above 0.25, above 0.30, above 0.35, above 0.40, above 0.45, above 0.50, above 0.55, and above 0.60, respectively.

[0083] Regarding the molar ratio (Y2O3 / B2O3) of the Y2O3 content relative to the B2O3 content, if the value of the molar ratio becomes smaller, there is a tendency for the refractive index of the glass to decrease, and if the value of the molar ratio becomes larger, there is a tendency for the glass to be easily crystallized. From the above viewpoints, the molar ratio (Y2O3 / B2O3) is 0.15 or more and 0.34 or less.

[0084] The molar ratio (Y2O3 / B2O3) is preferably 0.16 or more, and more preferably 0.17 or more, 0.18 or more, 0.19 or more, 0.20 or more, 0.21 or more, 0.22 or more, and 0.23 or more.

[0085] In addition, the molar ratio (Y2O3 / B2O3) is preferably 0.33 or less, and more preferably 0.32 or less, 0.31 or less, 0.30 or less, 0.29 or less, and 0.28 or less, respectively.

[0086] TiO2 is a component that increases the refractive index of glass. However, TiO2 is a component that reduces the transmittance of glass. If its content increases, the glass tends to be easily crystallized. From the above viewpoints, the TiO2 content is 5.00% or more and 30.00% or less.

[0087] The TiO2 content is preferably above 6.00%, and more preferably above 7.00%, above 8.00%, above 9.00%, above 10.00%, above 11.00%, above 12.00%, above 13.00%, above 14.00%, above 15.00%, above 15.50%, above 16.00%, above 16.50%, and above 17.00%.

[0088] In addition, the TiO2 content is preferably less than 29.00%, and more preferably less than 28.00%, less than 27.00%, less than 26.00%, less than 25.00%, less than 24.00%, less than 23.00%, less than 22.50%, less than 22.00%, less than 21.50%, less than 21.00%, and less than 20.50%.

[0089] The ZrO2 content is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. ZrO2 is a component that contributes to the high refractive index and low dispersion of glass. However, ZrO2 is a component that increases the viscosity of glass. If its content increases, the glass tends to lose clarity. From the above viewpoints, the ZrO2 content is 20.00% or less, preferably 19.00% or less, and more preferably 18.00% or less, 17.00% or less, 16.00% or less, 15.00% or less, 14.00% or less, 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, and 7.50% or less.

[0090] In addition, the ZrO2 content is preferably above 1.00%, and more preferably above 2.00%, above 2.50%, above 3.00%, above 3.50%, above 4.00%, above 4.50%, above 5.00%, above 5.50%, above 6.00%, and above 6.50%.

[0091] The content of Nb2O5 is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. Nb2O5 is a component that contributes to the high refractive index and low dispersion of glass. From the viewpoint of controlling the dispersion of glass, the content of Nb2O5 is 20.00% or less, preferably 19.00% or less, and more preferably 18.00% or less, 17.00% or less, 16.00% or less, 15.00% or less, 14.00% or less, 13.00% or less, 12.00% or less, 11.00% or less, 10.00% or less, 9.00% or less, 8.00% or less, 7.00% or less, 6.50% or less, 6.00% or less, 5.50% or less, 5.00% or less, and 4.50% or less.

[0092] In addition, the Nb2O5 content is preferably 0.10% or more, and more preferably 0.50% or more, 1.00% or more, and 1.50% or more, respectively.

[0093] From the viewpoint of inhibiting the crystallization of glass and inhibiting high dispersion, the total content of TiO2, ZrO2 and Nb2O5 (TiO2+ZrO2+Nb2O5) is less than 36.00%, preferably less than 34.00%, and more preferably less than 33.50%, less than 33.00%, less than 32.50%, less than 32.00%, less than 31.50%, less than 31.00%, less than 30.50%, less than 30.00%, and less than 29.50%, respectively.

[0094] From the viewpoint of increasing the refractive index of the glass, the total content (TiO2+ZrO2+Nb2O5) is above 23.00%, preferably above 24.00%, and more preferably above 24.50%, above 25.00%, above 25.50%, above 26.00%, above 26.50%, above 27.00%, above 27.50%, above 28.00%, and above 28.50%, respectively.

[0095] Regarding the molar ratio of TiO2 content to B2O3 content (TiO2 / B2O3), when the value of the molar ratio becomes larger, the glass tends to be highly dispersed, and when the value of the molar ratio becomes smaller, the refractive index of the glass tends to decrease. From the above viewpoints, the molar ratio (TiO2 / B2O3) is greater than 0.70 and less than 1.10.

[0096] The molar ratio (TiO2 / B2O3) is preferably 0.72 or more, and more preferably 0.74 or more, 0.75 or more, and 0.76 or more, respectively.

[0097] In addition, the molar ratio (TiO2 / B2O3) is preferably 1.09 or less, and more preferably 1.08 or less, 1.07 or less, 1.06 or less, 1.05 or less, 1.04 or less, and 1.03 or less, respectively.

[0098] If alkaline earth metal oxide is represented as RO and alkali metal oxide is represented as R2O, from the viewpoint of reducing the viscosity of the glass, the total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more, preferably 3.60% or more, and more preferably 3.70% or more, 3.80% or more, 3.90% or more, 4.00% or more, 4.10% or more, 4.20% or more, 4.30% or more, 4.40% or more, 4.50% or more, 4.60% or more, 4.70% or more, 4.80% or more, 4.90% or more, 5.00% or more, 5.10% or more, 5.20% or more, 5.30% or more, 5.40% or more, 5.50% or more, 5.60% or more, and 5.70% or more.

[0099] On the other hand, from the viewpoint of inhibiting the crystallization of glass, the total content (RO + R2O) is preferably 12.00% or less, and more preferably 11.50% or less, 11.00% or less, 10.50% or less, 10.00% or less, 9.50% or less, 9.00% or less, 8.50% or less, 8.00% or less, 7.50% or less, 7.40% or less, 7.30% or less, 7.20% or less, and 7.10% or less.

[0100] Regarding the content of each component of the alkali metal oxide R2O, the Li2O content is 0.00% or more, and may be 0.00% or more. From the viewpoint of further improving the thermal stability of the glass, suppressing the decrease in the glass transition temperature (thereby improving the machinability), and improving the chemical durability and weather resistance, the Li2O content is preferably 5.00% or less, and more preferably 4.00% or less, 3.00% or less, and 2.00% or less.

[0101] The content of each of Na2O, K2O, Rb2O and Cs2O is 0.00% or more, and may be 0.00% or more. Na2O, K2O, Rb2O and Cs2O all have the effect of improving the melting property of glass, but when their content increases, the thermal stability, chemical durability, weather resistance and machinability of glass tend to decrease. Therefore, the content of each of Na2O, K2O, Rb2O and Cs2O is preferably 5.00% or less, and more preferably 4.00% or less, 3.00% or less, and 2.00% or less, respectively.

[0102] Compared with Li2O, Na2O and K2O, Rb2O and Cs2O are expensive components and are not suitable for general-purpose glass. From the viewpoint of improving the meltability of the glass, lowering the glass transition temperature Tg and reducing the specific gravity of the glass while maintaining the thermal stability, chemical durability, weather resistance and machinability of the glass, the alkali metal oxide R2O contained in the above glass is one or more selected from the group consisting of Li2O, Na2O and K2O.

[0103] The alkaline earth metal oxide RO contained in the above glass is preferably one or more selected from the group consisting of MgO, CaO, SrO and BaO. The content of each of MgO, CaO, SrO and BaO is 0.00% or more, and can be 0.00% or more. From the viewpoint of suppressing the devitrification of the glass and achieving the desired optical properties, the content of each of MgO, CaO, SrO and BaO is preferably 8.00% or less, more preferably 7.00% or less, and further preferably 6.00% or less, 5.00% or less, 4.00% or less, 3.00% or less, and 2.00% or less.

[0104] Ta2O5 is an expensive component. From the viewpoint of reducing the cost of glass, the Ta2O5 content is preferably 2.50% or less, more preferably 2.00% or less, 1.50% or less, 1.00% or less, 0.50% or less, and most preferably 0.00%.

[0105] The Al2O3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. From the viewpoint of inhibiting glass crystallization, the Al2O3 content is preferably 2.00% or less, more preferably 1.50% or less, 1.00% or less, 0.50% or less, and most preferably 0.00%.

[0106] The WO3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. WO3 is a component that contributes to the high refractive index and low dispersion of glass, but when its content increases, the transmittance of glass tends to decrease. From the viewpoint of suppressing the decrease in the transmittance of glass, the WO3 content is preferably 0.40% or less, more preferably 0.30% or less, 0.20% or less, 0.10% or less, and most preferably 0.00%.

[0107] The Bi2O3 content is 0.00% or more, and can be 0.00%, 0.00% or more, or greater than 0.00%. Bi2O3 is a component that contributes to the high refractive index and low dispersion of glass, but when its content increases, the transmittance of glass tends to decrease. From the viewpoint of suppressing the decrease in the transmittance of glass, the Bi2O3 content is preferably 0.40% or less, more preferably 0.30% or less, 0.20% or less, 0.10% or less, and most preferably 0.00%.

[0108] The ZnO content is 0.00% or more, and can be 0.00%, 0.00% or more, or more than 0.00%. ZnO is a component that lowers the melting temperature of glass and also a component that lowers the glass transition temperature Tg. The ZnO content is preferably 0.10% or more, and more preferably 0.50% or more, 0.70% or more, 0.90% or more, and 1.00% or more.

[0109] On the other hand, from the viewpoint of suppressing crystallization of glass, the ZnO content is preferably 12.00% or less, and more preferably 11.00% or less, 10.00% or less, 9.00% or less, and 8.00% or less, in that order.

[0110] Regarding other glass components, considering the environmental impact, the As2O3 content is preferably 0.10% or less, more preferably 0.01% or less, and most preferably 0.00%. In addition, considering the environmental impact, the PbO content is preferably 1.00% or less, more preferably 0.50% or less, 0.10% or less, and most preferably 0.00%.

[0111] Sb2O3 is a component that can be added as a clarifier. A small amount of addition can also play a role in suppressing the reduction in light transmittance caused by the mixing of impurities such as Fe, but if the amount of Sb2O3 added is increased, the coloring of the glass tends to increase. Therefore, the amount of Sb2O3 added is preferably 0.00% or more and 0.10% or less, more preferably 0.00% or more and 0.08% or less, and further preferably 0.00% or more and 0.05% or less. The Sb2O3 content based on the external ratio refers to the Sb2O3 content expressed in mass % when the total content of the glass components other than Sb2O3 is set to 100 mass %.

[0112] SnO2 can also be added as a clarifier, but if it is added in excess of 1.00% in terms of external proportion, Sn becomes the starting point for nucleation and produces a tendency to devitrification when the glass is colored or heated, softened, and re-formed by press forming. Therefore, the amount of SnO2 added is preferably 0.00% or more and 1.00% or less, more preferably 0.00% or more and 0.50% or less, and preferably not added. The SnO2 content based on the external proportion refers to the content of SnO2 expressed in mass % when the total content of the glass components other than SnO2 is set to 100 mass %.

[0113] <Glass Properties>

[0114] (Refractive index nd)

[0115] The glass may be a high refractive index glass by having the glass composition. From the viewpoint of usefulness as a material for optical elements, the refractive index nd of the glass is preferably 1.9430 or more, more preferably 1.9450 or more, 1.9500 or more, and 1.9520 or more.

[0116] In addition, from the viewpoint of usefulness as a material for optical elements, the refractive index nd of the above-mentioned glass is preferably 1.9800 or less, and more preferably 1.9790 or less, 1.9780 or less, 1.99770 or less, 1.9760 or less, 1.9750 or less, 1.9740 or less, 1.9730 or less, 1.9720 or less, 1.9710 or less, 1.9700 or less, 1.9690 or less, 1.9680 or less, 1.9670 or less, 1.9660 or less, 1.9650 or less, 1.9640 or less, 1.9630 or less, 1.9620 or less, 1.9610 or less, 1.9600 or less, 1.9590 or less, 1.9580 or less, 1.9570 or less, 1.9560 or less, and 1.9550 or less.

[0117] (Abbe number νd)

[0118] The above-mentioned glass can exhibit low dispersion by having the above-mentioned glass composition.

[0119] From the viewpoint of usefulness as a material for an optical element, the Abbe number νd of the glass is preferably 30.00 or more, more preferably 30.20 or more, 30.50 or more, 31.00 or more, 31.50 or more, 32.00 or more, or 32.10 or more.

[0120] In addition, from the viewpoint of usefulness as a material for an optical element, the Abbe number νd of the above-mentioned glass is preferably 34.00 or less, and more preferably 33.50 or less, 33.00 or less, and 32.50 or less, respectively.

[0121] (proportion)

[0122] In the optical element constituting the optical system, the refractive power is determined by the refractive index of the glass constituting the optical element and the curvature of the optical functional surface (the surface where the light entering and exiting the optical element is to be controlled). When the curvature of the optical functional surface is to be increased, the thickness of the optical element is also increased. As a result, the optical element becomes heavier. In contrast, if a glass with a high refractive index is used, a large refractive power can be obtained even without increasing the curvature of the optical functional surface.

[0123] As described above, if the refractive index can be increased while suppressing an increase in the specific gravity of glass, it is possible to reduce the weight of an optical element having a certain refractive power.

[0124] From the above viewpoints, the specific gravity of the above-mentioned glass is preferably 5.50 or less, and more preferably 5.20 or less, 5.19 or less, 5.18 or less, 5.17 or less, 5.16 or less, 5.15 or less, 5.10 or less, 5.05 or less, and 5.00 or less.

[0125] The lower the specific gravity, the more preferred it is from the viewpoint of lightweighting of the optical element, so there is no particular lower limit to the specific gravity of the glass. In one embodiment, the specific gravity of the glass can be, for example, 4.80 or more, 4.85 or more, 4.90 or more, 4.92 or more, 4.93 or more, 4.94 or more, or 4.95 or more.

[0126] In the present invention and this specification, "specific gravity" is a value measured by the Archimedean method.

[0127] (Coloring degree λ5, λ 70 )

[0128] The light transmittance of glass, in detail, the light absorption end on the short wavelength side is suppressed from becoming longer wavelengths by the coloring degree λ5 and λ 70 The coloration degree λ5 represents the wavelength at which the spectral transmittance (including surface reflection loss) of glass with a thickness of 10±0.1 mm from the ultraviolet region to the visible region is 5%. 70 The wavelength at which the spectral transmittance is 70% as measured by the method described for λ5 is shown in the following table. 70 The spectral transmittance T (%) of the glass in the present invention and this specification is the intensity of light incident perpendicularly on one side of the two parallel planes of a glass sample after optical polishing, which is I in , the intensity of the light emitted from the other side through the glass sample is set to I out When , it is expressed as follows.

[0129] T(%)=I out / I in ×100

[0130] According to the coloring degree λ5 and λ 70 , the absorption end on the short wavelength side of the spectral transmittance can be quantitatively evaluated. For example, when a UV-curable adhesive is used to bond lenses together, the adhesive is irradiated with UV light through an optical element to cure the adhesive. From the perspective of efficiently curing the UV-curable adhesive, it is preferred that the absorption end on the short wavelength side of the spectral transmittance is in the short wavelength region. As an indicator for quantitatively evaluating the absorption end on the short wavelength side, the coloring degrees λ5 and λ 70 One or more of the.

[0131] The λ5 of the above-mentioned glass is preferably a λ5 that can represent 370nm or less. λ5 is more preferably 369nm or less, and further preferably 368nm or less. The shorter the wavelength of λ5, the more preferred it is, and the lower limit is not particularly limited. In one embodiment, λ5 can be 340nm or more, 341nm or more, 342nm or more, 343nm or more, 344nm or more, 345nm or more, 346nm or more, or 347nm or more.

[0132] The glass is preferably capable of expressing a wavelength of λ below 440 nm. 70 . 70 More preferably, the wavelength is 439 nm or less, 438 nm or less, 437 nm or less, 436 nm or less, 435 nm or less, 434 nm or less, 433 nm or less, 432 nm or less, 431 nm or less, 430 nm or less, 429 nm or less, 428 nm or less, and 427 nm or less. 70 The shorter the wavelength, the more preferred, and there is no particular lower limit. In one embodiment, λ 70 It may be above 390 nm, above 391 nm, above 392 nm, above 393 nm or above 394 nm.

[0133] (Glass transition temperature Tg)

[0134] From the viewpoint of machinability (specifically, the viewpoint that the glass is not easily broken during mechanical processing such as cutting, cutting, grinding and polishing), the glass transition temperature Tg of the above-mentioned glass is preferably 680°C or above, and more preferably 685°C or above, 686°C or above, 687°C or above, 688°C or above, 690°C or above, 691°C or above, 692°C or above, 693°C or above, 694°C or above, 695°C or above, 696°C or above, 697°C or above, 698°C or above, 699°C or above, and 700°C or above.

[0135] On the other hand, from the viewpoint of reducing the burden on the annealing furnace or the forming mold, the glass transition temperature Tg of the above-mentioned glass is preferably below 750°C, and more preferably below 750°C, below 745°C, below 744°C, below 743°C, below 742°C, below 741°C, below 740°C, below 735°C, below 730°C, and below 725°C, respectively.

[0136] The glass transition temperature Tg was determined using a differential scanning calorimeter at a temperature increase rate of 10° C. / min.

[0137] <Method for producing optical glass>

[0138] In order to obtain the target glass composition, the above optical glass is prepared by weighing and blending oxides, carbonates, sulfates, nitrates, hydroxides, etc. as raw materials, fully mixing them as a mixed batch, heating and melting them in a melting container, degassing and stirring them, and making a homogeneous and bubble-free molten glass, which can be obtained by shaping it. Specifically, it can be made using a known melting method.

[0139] [Glass material for press molding, optical element blank, and method for producing the same]

[0140] Another aspect of the present invention relates to a glass material for press molding composed of the above optical glass;

[0141] The optical element blank is formed from the above optical glass.

[0142] According to another aspect of the present invention, there is also provided a method for producing a press-molding glass material, which comprises the step of molding the above-mentioned optical glass into a press-molding glass material.

[0143] A method for manufacturing an optical element blank, comprising the steps of making the optical element blank by stamping the above-mentioned optical glass stamping glass raw material using a stamping die;

[0144] A method for producing an optical element blank comprising the step of forming the optical glass into an optical element blank.

[0145] The so-called optical element blank is an optical element base material that is similar to the shape of the target optical element, and the grinding amount (surface layer removed by grinding) and the grinding amount (surface layer removed by grinding) as required are added to the shape of the optical element. The optical element is completed by grinding and polishing the surface of the optical element blank. In one method, the optical element blank can be made by a method (called direct stamping method) of stamping and forming molten glass obtained by melting the above-mentioned glass in an appropriate amount. In another method, the optical element blank can also be made by solidifying the molten glass obtained by melting the above-mentioned glass in an appropriate amount.

[0146] In another embodiment, an optical element blank can be produced by preparing a press-molding glass material and press-molding the prepared press-molding glass material.

[0147] The press-forming of the glass raw material for press forming can be performed by a known method of using a press-forming die to press the glass raw material for press forming in a heated and softened state. Both the heating and the press-forming can be performed in the atmosphere. By annealing after the press-forming to reduce the deformation inside the glass, a homogeneous optical element blank can be obtained.

[0148] In addition to materials called glass blocks for press forming used for press forming of optical element blanks in their original state, press forming glass raw materials also include materials that are subjected to mechanical processing such as cutting, grinding, and polishing and are used for press forming via glass blocks for press forming. As a cutting method, there are methods of forming a groove in the portion to be cut on the surface of the glass plate by a method called scribing, applying local pressure to the groove portion from the back of the groove-forming surface, and cutting the glass plate at the groove portion, or a method of cutting the glass plate using a cutting blade, etc. In addition, as grinding and polishing methods, drum polishing, etc. can be cited.

[0149] The glass raw material for press forming can be produced, for example, by casting molten glass into a casting mold to form a glass plate, and cutting the glass plate into a plurality of glass sheets. Alternatively, a suitable amount of molten glass can be formed to produce a glass block for press forming. The optical element blank can also be produced by reheating, softening and press forming the glass block for press forming. The method of reheating, softening and press forming the glass to produce the optical element blank is called a reheating press method relative to the direct press method.

[0150] [Optical element and method of manufacturing the same]

[0151] Another aspect of the present invention relates to an optical element composed of the above optical glass.

[0152] The optical element is made of the optical glass. In the optical element, one or more layers of coatings such as multilayer films such as anti-reflection films may be formed on the glass surface.

[0153] According to one aspect of the present invention, there is also provided a method for producing an optical element, comprising the step of producing an optical element by grinding and / or polishing the optical element blank.

[0154] In the manufacturing method of the above optical element, mechanical processing such as grinding and lapping can be performed by a known method, and an optical element with high internal quality and surface quality can be obtained by fully cleaning and drying the surface of the optical element after processing. In this way, an optical element composed of the above optical glass can be obtained. As the optical element, various lenses such as spherical lenses, aspherical lenses, micro lenses, prisms, etc. can be exemplified.

[0155] In addition, the optical element composed of the above optical glass is also suitable as a lens constituting a joined optical element. As a joined optical element, there can be exemplified an element formed by joining lenses to each other (joined lens), an element formed by joining a lens and a prism, and the like. For example, a joined optical element can be made by precision machining the joining surfaces of the two joined optical elements (for example, spherical grinding) to make the shape into an inverted shape, applying a UV-curable adhesive for bonding the joined lenses and bonding them, and then irradiating the lens with ultraviolet light to cure the adhesive, thereby making it. In order to make a joined optical element in this way, the above optical glass is preferred. By using a plurality of glasses with different Abbe numbers νd to separately make and join a plurality of joined optical elements, it is possible to make an element suitable for chromatic aberration correction.

[0156] [Example]

[0157] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to the embodiments shown in the examples.

[0158] [Example 1]

[0159] <No.001~118>

[0160] Nitrates, sulfates, carbonates, hydroxides, oxides, boric acid, etc. corresponding to the raw materials for introducing the respective components are weighed and sufficiently mixed to obtain the glass composition (unit: mol %) shown in the following table.

[0161] The blended raw materials were placed in a platinum crucible, heated and melted in a furnace set at 1350°C for 2 hours. After the molten glass was stirred and homogenized, the molten glass was poured into a preheated mold, and immediately placed in an annealing furnace after cooling to near the glass transition temperature, and kept at a temperature around the glass transition temperature for about 30 minutes, then slowly cooled at a slow cooling rate of -30°C / hour for 4 hours, and then cooled in the furnace to room temperature to obtain the optical glasses No. 001 to 118 shown in the following table.

[0162] The physical properties of the optical glass obtained in this way are shown in the following table.

[0163] Various physical properties of the optical glass were measured by the methods shown below.

[0164] <Evaluation of Physical Properties of Optical Glass>

[0165] (1) Refractive index nd Abbe number νd

[0166] The refractive index nd and the Abbe number νd of the obtained glass were measured by a refractive index measurement method in accordance with the standards of the Japan Optical Glass Industries Association.

[0167] (2) Glass transition temperature Tg

[0168] The glass was fully pulverized in a mortar as a sample, and the glass transition temperature Tg was measured using a differential scanning calorimeter (DSC8271) manufactured by Rigaku Corporation at a heating rate of 10° C. / min using a platinum cell as a sample container.

[0169] (3) Specific gravity

[0170] Determine specific gravity by Archimedes method.

[0171] 4) Coloring degree λ5, λ 70

[0172] A glass sample with a thickness of 10±0.1 mm and two optically polished surfaces facing each other was used to measure the spectral transmittance T (%) by a spectrophotometer. The wavelength (nm) at which T is 5% is λ5, and the wavelength (nm) at which T is 70% is λ 70 .

[0173]

Table 1

[0174]

[0175]

[0176]

[0177]

[0178]

[0179]

[0180]

[0181]

[0182]

[0183]

[0184]

[0185] [Example 2]

[0186] The various glasses obtained in Example 1 were used to prepare glass blocks for press molding (glass blocks). The glass blocks were heated and softened in the atmosphere, and press molded using a press mold to prepare lens blanks (optical element blanks). The prepared lens blanks were taken out of the press mold, annealed, and subjected to mechanical processing including grinding to prepare spherical lenses composed of the various glasses prepared in Example 1.

[0187] [Example 3]

[0188] The molten glass prepared in Example 1 is pressed in a desired amount using a press forming die to prepare a lens blank (optical element blank). The prepared lens blank is taken out from the press forming die, annealed, and subjected to mechanical processing including grinding to prepare a spherical lens composed of the various glasses prepared in Example 1.

[0189] [Example 4]

[0190] The glass block (optical element blank) produced by solidifying the molten glass produced in Example 1 was annealed and subjected to mechanical processing including grinding, thereby producing spherical lenses composed of the various glasses produced in Example 1.

[0191] [Example 5]

[0192] The spherical lens produced in Examples 2 to 4 is bonded to a spherical lens made of other types of glass to produce a joined lens. The bonding surface of the spherical lens produced in Examples 2 to 4 is a convex surface, and the bonding surface of the spherical lens made of other types of glass is a concave surface. The two bonding surfaces are produced in such a way that the absolute values ​​of the radii of curvature are equal to each other. An ultraviolet curing adhesive for bonding optical elements is applied to the bonding surface, and the two lenses are bonded to each other on the bonding surface. Then, the adhesive applied on the bonding surface is irradiated with ultraviolet rays through the spherical lens produced in Examples 2 to 4 to cure the adhesive.

[0193] The cemented lens was manufactured as described above. The cemented lens had a sufficiently high bonding strength and a sufficient level of optical performance.

[0194] The embodiments disclosed this time should be considered as illustrative in all aspects and not restrictive. The scope of the present invention is indicated by the claims rather than the above description, and the purpose is to include all modifications within the meaning and scope equivalent to the claims.

[0195] For example, by adjusting the composition described in the specification to the glass composition exemplified above, the optical glass of one embodiment of the present invention can be obtained.

[0196] Furthermore, it is of course possible to arbitrarily combine two or more items described as examples or preferred ranges in the specification.

Claims

1. An optical glass, wherein: In the glass composition expressed in mol% on an oxide basis, The SiO2 content is 1.00% or more and 30.00% or less, The B2O3 content is 1.00% or more and 40.00% or less, The La2O3 content is 5.00% or more and 40.00% or less, The Gd2O3 content is 0.00% or more and 3.50% or less, The Y2O3 content is 0.50% or more and 20.00% or less, The TiO2 content is 5.00% or more and 30.00% or less, The ZrO2 content is 0.00% or more and 20.00% or less, The Nb2O5 content is 0.00% or more and 20.00% or less, The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is 0.00% or more and 3.50% or less, The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is more than 26.50%, The total content of TiO2, ZrO2 and Nb2O5 (TiO2+ZrO2+Nb2O5) is 23.00% or more and 36.00% or less, The total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more, The molar ratio of the Gd2O3 content to the SiO2 content (Gd2O3 / SiO2) is greater than or equal to 0.00 and less than or equal to 0.23, The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 0.80 or more and 1.56 or less, The molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is 0.87 or less, The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.15 or more and 0.34 or less, and The molar ratio of the TiO2 content to the B2O3 content (TiO2 / B2O3) is greater than or equal to 0.70 and less than or equal to 1.

10.

2. The optical glass according to claim 1, wherein: The Al2O3 content is greater than or equal to 0.00% and less than or equal to 2.00%.

3. The optical glass according to claim 1, wherein: The Nb2O5 content is greater than or equal to 0.10% and less than or equal to 20.00%.

4. The optical glass according to claim 1, wherein: The WO3 content is 0.00% or more and 0.40% or less.

5. The optical glass according to claim 1, wherein: The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less.

6. The optical glass according to claim 1, wherein: The total content of the alkaline earth metal oxide RO and the alkali metal oxide R2O (RO+R2O) is 3.50% or more and 10.50% or less.

7. The optical glass according to claim 1, wherein: The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is greater than or equal to 0.17 and less than or equal to 0.

34.

8. The optical glass according to claim 1, wherein: The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is greater than or equal to 1.20 and less than or equal to 1.

56.

9. The optical glass according to claim 1, wherein: The molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is greater than or equal to 0.50 and less than or equal to 0.

87.

10. The optical glass according to claim 1, wherein: The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is greater than or equal to 0.00% and less than or equal to 2.50%.

11. The optical glass according to claim 1, wherein: The Al2O3 content is 0.00% or more and 2.00% or less, The Nb2O5 content is 0.10% or more and 20.00% or less, The WO3 content is 0.00% or more and 0.40% or less, The total content of La2O3, Gd2O3 and Y2O3 (La2O3+Gd2O3+Y2O3) is 26.50% or more and 35.00% or less, The total content of alkaline earth metal oxide RO and alkali metal oxide R2O (RO+R2O) is 3.50% or more and 10.50% or less, The molar ratio of the Y2O3 content to the B2O3 content (Y2O3 / B2O3) is 0.17 or more and 0.34 or less, The molar ratio of the B2O3 content to the SiO2 content (B2O3 / SiO2) is 1.20 or more and 1.56 or less, The molar ratio of SiO2 content to La2O3 content (SiO2 / La2O3) is 0.50 or more and 0.87 or less, and The total content of Gd2O3 and Ta2O5 (Gd2O3+Ta2O5) is greater than or equal to 0.00% and less than or equal to 2.50%.

12. An optical element, wherein: The optical glass is composed of any one of claims 1 to 11.

Citation Information

Cited By

  • Optical glass with high refractive index, preparation method thereof and optical element

    CN122520336A